2022
DOI: 10.3390/antiox11071346
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory, Antioxidant, and Skin Regenerative Potential of Secondary Metabolites from Plants of the Brassicaceae Family: A Systematic Review of In Vitro and In Vivo Preclinical Evidence (Biological Activities Brassicaceae Skin Diseases)

Abstract: The Brassicaceae family constitutes some of the most well-studied natural products in the world, due to their anti-inflammatory, anti-oxidative, and pro-regenerative properties as well as their ubiquitous distribution across the world. To evaluate the potential efficacy of the Brassicaceae family in the treatment of inflammatory skin disorders and wounds, based on preclinical evidence from in vivo and in vitro studies. This systematic review was performed according to the PRISMA guidelines, using a structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…A review has recently reported that, upon fractionation, plant extracts frequently lose their biological activities, suggesting that the exerted effects result from the whole phytocomplex, acting synergistically or additively, rather than a single fraction or compound [ 42 ]. Several studies reported that secondary metabolites from the Brassicaceae family, including kaempferol, possess valuable in vitro and in vivo anti-inflammatory and antioxidant activities [ 30 ], in agreement with our findings confirming the high potential of B. drepanensis extract in counteracting the early stages of oxidative stress and inflammation, which are transversals in many pathological conditions, including obesity and its associated complications, such as type 2 diabetes [ 29 , 43 ]. The effects of natural compounds on metabolic disorders differ, and include amelioration in energy expenditure, insulin secretion, glucose utilization, satiety, or beneficial interference with the gut microbiome [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A review has recently reported that, upon fractionation, plant extracts frequently lose their biological activities, suggesting that the exerted effects result from the whole phytocomplex, acting synergistically or additively, rather than a single fraction or compound [ 42 ]. Several studies reported that secondary metabolites from the Brassicaceae family, including kaempferol, possess valuable in vitro and in vivo anti-inflammatory and antioxidant activities [ 30 ], in agreement with our findings confirming the high potential of B. drepanensis extract in counteracting the early stages of oxidative stress and inflammation, which are transversals in many pathological conditions, including obesity and its associated complications, such as type 2 diabetes [ 29 , 43 ]. The effects of natural compounds on metabolic disorders differ, and include amelioration in energy expenditure, insulin secretion, glucose utilization, satiety, or beneficial interference with the gut microbiome [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…Many in vitro and in vivo studies support the anti-inflammatory effect of phytochemicals from different Brassica spp. and their cultivated varieties [ 30 ]. B. drepanensis is a wild relative of cultivated cabbages.…”
Section: Discussionmentioning
confidence: 99%
“…Brassica species harbor an impressive repertoire of nutrients such as minerals, essential vitamins, carbohydrates, and phytochemicals, including phenolic compounds, glucosinolates and their breakdown products (isothiocyanates and indoles), carotenoids, and seed oils, recognized as bioactive secondary metabolites [5]. The metabolites synthesized by each species are responsible for providing a unique and distinct taste as well as exhibiting broadly interesting and beneficial bioactivities such as antioxidant [3], anti-inflammatory [6], antimicrobial [7], and anticancer bioactivities [8].…”
Section: Introductionmentioning
confidence: 99%
“…These models will enable us to measure and monitor different stages of wound healing, especially the inflammatory and proliferative phases. Some studies tend to use male animals more frequently due to the impact of hormonal cycles in females and their heightened sensitivity to toxicity [ 237 ]. The in vivo evaluation of dual-growth factor-releasing meshes on rat skin wounds yielded promising results [ 238 ].…”
Section: In-vivo Studiesmentioning
confidence: 99%